2011
DOI: 10.1029/2011jg001709
|View full text |Cite
|
Sign up to set email alerts
|

Lakes as buffers of stream dissolved organic matter (DOM) variability: Temporal patterns of DOM characteristics in mountain stream-lake systems

Abstract: [1] Lakes within fluvial networks may affect dissolved organic matter (DOM) dynamics in streams by dampening spring DOM snowmelt flushing responses and/or by increasing summer DOM production. We assessed the temporal variability of dissolved organic carbon (DOC) concentration and DOM characteristics (specific ultraviolet absorbance (SUVA 254 ); DOC:dissolved organic nitrogen (DOC:DON)), as well as DOC export in seven paired lake inflows and outflows in the Sawtooth Mountain lake district, Idaho. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 82 publications
7
66
0
1
Order By: Relevance
“…In comparison, peak concentrations of OC coincided with peak discharge below Fontenelle reservoir, which was likely driven by a combination of factors including dam operations and longer residence time of water in the reservoir relative to the river. For instance, a similar finding of peak OC concentration with peak discharge was found below natural alpine lakes in Idaho, USA, which was attributed to residence time of the lake (Goodman et al, 2011). Riverine DOC sources, and therefore bioavailability and composition, can be seasonally dependent.…”
Section: Temporal Oc Dynamicssupporting
confidence: 54%
See 1 more Smart Citation
“…In comparison, peak concentrations of OC coincided with peak discharge below Fontenelle reservoir, which was likely driven by a combination of factors including dam operations and longer residence time of water in the reservoir relative to the river. For instance, a similar finding of peak OC concentration with peak discharge was found below natural alpine lakes in Idaho, USA, which was attributed to residence time of the lake (Goodman et al, 2011). Riverine DOC sources, and therefore bioavailability and composition, can be seasonally dependent.…”
Section: Temporal Oc Dynamicssupporting
confidence: 54%
“…Reservoirs on rivers may trap particulate OC (POC) (Friedl and Wüest, 2002;Downing et al, 2008;Tranvik et al, 2009) and transform and produce dissolved OC (DOC) (Mash et al, 2004;Knoll et al, 2013). Increased water residence time (Vörösmarty et al, 1997;Sabo et al, 2010) allows for OC to be respired, incorporated into microbial production, or buried while production of autochthonous or microbial DOC increases (Mash et al, 2004;Knoll et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of DON in the Timbercreek Farm pond's outflow changed seasonally; in the winter, DON was 10-30% of the TDN flux and in the summer and fall, 40-50% of the TDN (Chaffin 2016). A similar study found that both dissolved organic matter and DON increased in a pond's outflow in the summer (Goodman et al 2011). This seasonal pattern suggests that primary production (and subsequent decomposition) is important in controlling DON:DIN ratios in the pond's outflow (Chaffin 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Naturally occurring lakes are often sinks of DIN, but sources of DON (Goodman et al 2011). DON fluxes into and out of agricultural impoundments are often highly variable (Powers et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation